ANALISIS PENGARUH BRAND IMAGE, BRAND AWARENESS, e-WOM DENGAN TRUST SEBAGAI VARIABEL MEDIASI TERHADAP PURCHASE INTENTION SKINCARE KOREA DI KOTA BATAM - Ria Hartoko; Johny Budiman (Departemen Manajemen, 2022)
This study aims to analyze the influence of brand image, brand awareness, e-WOM on purchase intention mediated by trust. The number of sample needs is 405 respondent data with data collection using purposive sampling. The analysis technique in this study applies validity and reliability tests as well as path analysis test using Smart PLS. Based on the results of the analysis that has been carried out, it proves that there is a significant positive effect of brand image, brand awareness and e-WOM on trust, the effect of trust on purchase intention, the effect of brand image, brand awareness and e-WOM on purchase intention and trust successfully mediates between brand image, brand awareness, and eWOM on purchase intention.